Quantifying the biochemical state of knee cartilage in response to running using T1rho magnetic resonance imaging - Heckelman, Lauren N. (Sci Rep, 2020)
Roughly 20% of Americans run annually, yet how this exercise influences knee cartilage health is poorly understood. To address this question, quantitative magnetic resonance imaging (MRI) can be used to infer the biochemical state of cartilage. Specifically, T1rho relaxation times are inversely related to the proteoglycan concentration in cartilage. In this study, T1rho MRI was performed on the dominant knee of eight asymptomatic, male runners before, immediately after, and 24 hours after running 3 and 10 miles. Overall, (mean ± SEM) patellar, tibial, and femoral cartilage T1rho relaxation times significantly decreased immediately after running 3 (65 ± 3 ms to 62 ± 3 ms; p = 0.04) and 10 (69 ± 4 ms to 62 ± 3 ms; p < 0.001) miles. No significant differences between pre-exercise and recovery T1rho values were observed for either distance (3 mile: p = 0.8; 10 mile: p = 0.08). Percent decreases in T1rho relaxation times were significantly larger following 10 mile runs as compared to 3 mile runs (11 ± 1% vs. 4 ± 1%; p = 0.02). This data suggests that alterations to the relative proteoglycan concentration of knee cartilage due to water flow are mitigated within 24 hours of running up to 10 miles. This information may inform safe exercise and recovery protocols in asymptomatic male runners by characterizing running-induced changes in knee cartilage composition.